N-β-alanyldopamine metabolism, locomotor activity and sleep in Drosophila melanogaster ebony and tan mutants - Rossi, Fabiana Alejandra (2015)
Drosophila melanogaster Meigen mutants for N-β-alanyldopamine (NBAD) metabolism have altered levels of NBAD, dopamine and other neurotransmitters. The ebony1 mutant strain has very low levels of NBAD and higher levels of dopamine, whereas the opposite situation is observed in the tan1 mutant. Dopamine is implicated in the control of movement, memory and arousal, as well as in the regulation of sleep and wakefulness in D. melanogaster. N-β-alanyldopamine, which is best known as a cuticle cross-linking agent, is also present in nervous tissue and has been proposed to promote locomotor activity in this fly. The daily locomotor activity and the sleep patterns of ebony1 and tan1 mutants are analyzed, and are compared with wild-type flies. The tan1 mutant shows reduced locomotor activity, whereas ebony1 shows higher levels of activity than wild-type flies, suggesting that NBAD does not promote locomotor activity. Both mutants spend less time asleep than wild-type flies during night-time; ebony shows more consolidated activity during night-time and increased sleep latency, whereas tan is unable to consolidate locomotor activity and sleep in either phase of the day. The daily level of NBAD-synthase activity is measured in vitro using wild-type and tan1 protein extracts, and the lowest NBAD synthesis is observed at the time of higher locomotor activity. The abnormalities in several parameters of the waking/sleep cycle indicate some dysfunction in the processes that regulates these behaviours in both mutants.